2020
DOI: 10.1039/d0en00309c
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene nano- and microplastic accumulation at Arabidopsis and wheat root cap cells, but no evidence for uptake into roots

Abstract: Association of plastic particles with plant roots could represent a pathway for human consumption of plastic and plastic-associated organic contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(54 citation statements)
references
References 55 publications
1
51
1
1
Order By: Relevance
“…[83] And, Taylor et al found the accumulation of micro and nano spheres of PS in the root cap of A. thaliana and Triticum aestivum, but no evidence of uptake or negative effects. [85] Dose-dependent decreases in mitotic index have been reported in A. cepa [82,89] and in V. faba [90] seedlings exposed to PS nanoparticles. In the case of A. cepa, the presence of nanoplastics inside cells interfering with some organelles was reported for the first time.…”
Section: Toxicity Mechanismsmentioning
confidence: 98%
See 1 more Smart Citation
“…[83] And, Taylor et al found the accumulation of micro and nano spheres of PS in the root cap of A. thaliana and Triticum aestivum, but no evidence of uptake or negative effects. [85] Dose-dependent decreases in mitotic index have been reported in A. cepa [82,89] and in V. faba [90] seedlings exposed to PS nanoparticles. In the case of A. cepa, the presence of nanoplastics inside cells interfering with some organelles was reported for the first time.…”
Section: Toxicity Mechanismsmentioning
confidence: 98%
“…[131] However, it was unsuccessful to detect PS in the roots of A. thaliana and T. aestivum because of the interference with styrene peak, which can be a degradation product of the pyrolysis of plant tissues. [85] TED-GC-MS combines thermo gravimetric analysis for thermal degradation and solid phase extraction for identification of plastics in environmental samples. [140] Recently, Bolea-Fernandez et al presented a new approach based on ICP-MS detection operated in single-event mode or single particle (SP) ICP-MS mode.…”
Section: Mass Spectrometry Based Techniquesmentioning
confidence: 99%
“…They observed PSNPs particles in the xylem of the root and shoot, suggesting that NPs could enter the root cells via the epidermis or rhizodermis through the intercellwall path (Jiang et al, 2019;Zhang et al, 2019). Taylor et al (2020) used CLSM and pyrolysis gas chromatography-mass spectrometry to detect PE nanospheres and microspheres in wheat and Arabidopsis plants. They observed MPs on the root surface but found no evidence of its presence in internal root structures.…”
Section: Detection and Analysis Of Mps And Nps In Plant Systemsmentioning
confidence: 99%
“…A recent study from Bosker et al (2020), showed that MPs can accumulate on pores in seed capsule and delay germination and root growth of Lepidium sativum terrestrial vascular plants [ 7 ]. On the contrary, studies on Arabidopsis and wheat showed that no MPs accumulated in plant tissues beyond root cap [ 10 ], while Zhang et al (2015) reported that high concentrations of LDPE particles can improve soil fertility [ 11 ].…”
Section: Introductionmentioning
confidence: 99%